2015
DOI: 10.19052/ed.3685
|View full text |Cite
|
Sign up to set email alerts
|

Discapacidad: una construcción narrativa excluyente

Abstract: <p align="justify">La identidad que la cultura atribuye a las personas con discapacidad está sustentada en narrativas de exclusión que se traducen en modelos discursivos de discriminación y abuso de poder, representados en normas y estereotipos excluyentes que niegan sus capacidades y atentan contra su reconocimiento para participar en condiciones de igualdad en la vida social y política. En este sentido, el análisis de las narrativas excluyentes permite develar dichas prácticas discriminatorias. El docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
1
0
5
Order By: Relevance
“…According to Erikson, the need to form a strong identity is critical; however, disabilities could impede the discovery of self-identity because of disabilities lead to experiences of ostracism and exclusion. As different studies have reported, people with disabilities experience social discrimination (Baquero, 2015) and school exclusion (Jiménez & Huete, 2002;Mañas, González & Cortés, 2020;Mogensen & Mason, 2015;Savaria, Underwood & Sinclair, 2011) and limitations to participate fully in the social and educational contexts in which they are immersed (Gómez & Cardona, 2010), generating the construction of a disability identity. According to Forber-Pratt, Lyew, Mueller, and Samples (2017), the identity of the disability can be defined as the unique and particular capacity that a person with a disability has to perceive himself, his body, and his way of interacting with the world and is related to the experience and social perception of the person with disabilities (Hopson, 2019).…”
Section: Self-identity Among People With Learning or Physical Disabil...mentioning
confidence: 99%
“…According to Erikson, the need to form a strong identity is critical; however, disabilities could impede the discovery of self-identity because of disabilities lead to experiences of ostracism and exclusion. As different studies have reported, people with disabilities experience social discrimination (Baquero, 2015) and school exclusion (Jiménez & Huete, 2002;Mañas, González & Cortés, 2020;Mogensen & Mason, 2015;Savaria, Underwood & Sinclair, 2011) and limitations to participate fully in the social and educational contexts in which they are immersed (Gómez & Cardona, 2010), generating the construction of a disability identity. According to Forber-Pratt, Lyew, Mueller, and Samples (2017), the identity of the disability can be defined as the unique and particular capacity that a person with a disability has to perceive himself, his body, and his way of interacting with the world and is related to the experience and social perception of the person with disabilities (Hopson, 2019).…”
Section: Self-identity Among People With Learning or Physical Disabil...mentioning
confidence: 99%
“…En un inicio, las personas con discapacidad, al igual que los enfermos mentales y los homosexuales, sufrieron de persecución, ostracismo y menosprecio. Su identidad histórica fue marcada por la exclusión, los prejuicios y los estereotipos de un pasado latente que han hecho de la discriminación y el aislamiento una constante (Baquero, 2015). Incluso el concepto de discapacidad en sí es novedoso, pues por la mayor parte de la historia se los llamó personas con defectos físicos, inválidos, minusválidos o deficientes (Samaniego, 2009).…”
Section: De La Exclusión a La Inclusión: La Evolución Sociohistórica unclassified
“…Pasan a ser vistas como prescindibles en la sociedad puesto que se los considera inhábiles para producir (Palacios, 2008). La respuesta usual ante la discapacidad era la marginación, internamiento y reclusión forzada, ignorando aspectos cruciales como la educación e inserción laboral (Baquero, 2015).…”
Section: De La Exclusión a La Inclusión: La Evolución Sociohistórica unclassified
See 1 more Smart Citation
“…En un inicio, las personas con discapacidad, al igual que los enfermos mentales y los homosexuales, sufrieron de persecución, aislamiento y menosprecio. Su identidad histórica fue marcada por la exclusión, los prejuicios y los estereotipos de un pasado latente que han hecho de la discriminación y el aislamiento una constante (Baquero, 2015).…”
Section: Introductionunclassified